Operative treatment of paediatric penetrating head injuries in southern Afghanistan. (August 2013) - Mathew, P.; Gibbons, A. J.; Christie, M.; Eisenburg, M. F.
Abstract: The operative management and early post-operative outcome of 16 consecutive cases of paediatric penetrating head injury treated by a single surgeon at a military trauma centre in Southern Afghanistan are retrospectively analysed. The majority of cases of injury were caused by fragments from exploding munitions. The aim of neurosurgical intervention in penetrating head injury is the prevention of wound infection and treatment or prevention of a critical rise in intracranial pressure. In 14 cases in this study, these aims were fulfilled without resort to brain resection, although a delayed cranioplasty procedure was required in 6 patients. Despite the ongoing conflict, families, local communities and coalition forces transport teams combine to make the latter a viable option in Southern Afghanistan, with an excellent short-term outcome.